Usefulness of ultrasonography and color Doppler sonography in the diagnosis of major salivary gland diseases - G.M. Giuseppetti; D. Salera; G. Argalia; M. Carotti; F. Salaffi; W. Grassi (PAGEPress Publications, 2011)
The algorithm for imaging of the salivary glands depends on the clinical scenario with which the patient presents to the clinician. Ultrasound has been increasingly used in recent years and thanks to high performance, easy to use apparatus, it can now be used for exploration of the salivary glands. This non invasive, painless and relatively inexpensive examination provides rapid visualisation of the salivary glands and is a useful adjunct to computed tomography and magnetic risonance imaging examination, particularly in tumour pathology. In recent years, publications have highlighted the potential uselfulness of salivary gland ultrasonography as a simple and non-invasive adjunctive test for the detection of gland involvement in Sjögren's syndrome (SS). SS is a chronic inflammatory disease of the salivary glands characterised by focal lymphocytic infiltrates that cause progressive destruction of the acinar structures. The findings of a previous study lead us to believe, in agreement with other examiners, that semiquantitative assessment of ultrasonographic images of the salivary glands is a sensitive and very useful means of evaluating salivary involvement in SS. Color Doppler sonography is a recently introduced method which makes it possible to evaluate intra- and perilesional vascularization and to perform a hemodynamic study of the area being explored. The color Doppler sonography can provide a useful adjunct to conventional ultrasound, increasing diagnostic accuracy in submandibular- parotid masses and to analyze physiologic changes that occur during salivary stimulation in normal subjects and the flow alterations that occur in diseased glands of SS patients. This article reviews the normal ultrasound anatomy of the salivary glands along with lithiasic, inflammatory, tumoral, and autoimmune disease such as SS.